HIV partner notification policy and practice within GUM clinics in England: where are we now?. Issue 1 (February 1997) - Fenton, K A; Copas, A; Johnson, A M; French, R; Petruckevitch, A; Adler, M W
Abstract : OBJECTIVES: To evaluate the extent to which larger genitourinary medicine (GUM) clinics in England have established local clinic policies for HIV Partner Notification (PN) and to describe the process of HIV PN within this setting. DESIGN: A cross-sectional survey of HIV PN policies and practices within GUM clinics. SUBJECTS AND SETTING: Senior consultants in 59 GUM clinics in England. MAIN OUTCOME MEASURES: The presence of clinic policies for HIV PN, indicators of HIV PN activity (that is, its initiation, documentation, performance and evaluation) and factors hindering the acceptance of HIV PN into clinical practice. RESULTS: Only 18% (10/57) of respondents stated that their clinics had developed their own local policies for HIV PN. Fifteen percent (9/58) of clinics had audited HIV PN activity, 15% had provided specific HIV PN training for doctors and 47% (27/58) for health advisers. Within GUM clinics, health advisers play a key role in the HIV PN process, being responsible for initiating the discussion of partners, patient follow-up and documenting HIV PN activity in patients' notes. Notifying partners was primarily seen as the responsibility of the newly diagnosed HIV positive patient. Although 77% (43/56) of responding consultants believed that HIV PN had become an accepted part of their clinics' practice, the perceived unacceptability of HIV PN to patients and health care workers were seen as important limiting factors. CONCLUSION: In many GUM clinics, local policies on HIV PN have yet to be established and appropriate training for the health personnel provided. Nevertheless, there appears to be wide-spread acceptance of HIV PN in clinical practice with an acknowledgement of its limiting factors. Further research into the acceptability of HIV PN to health care workers and patients in this setting should be undertaken.